Implementasi Metode Komunikasi Persuasif pada Mata Pelajaran Al-Quran Hadits Siswa Kelas VIII di SMP Darussalam Kalibaru Tahun Pelajaran 2023/2024 - Afrida Nur Laili; Yuda Pratama (LPPM Politeknik Pratama, 2024)
This research aims to determine the implementation of persuasive methods in learning Al-Qur'an and Hadith subjects for class VIII students at SMP Darussalam Kalibaru in the 2023/2024 academic year. The research method used is classroom action research (PTK) with the application of two cycles. The research sample involved 20 students. The research results showed a significant increase in student learning outcomes, from 40% at the start of the study to 95%. Data analysis shows that the implementation of persuasive communication methods in teaching Al-Qur'an and Hadith subjects at Darussalam Kalibaru Middle School has proven to be very effective. The results achieved provide a positive picture of the potential of this method in increasing students' understanding and engagement in learning. These findings provide an important contribution to the practical understanding of the use of persuasive methods in the context of learning the Koran and Hadith in the educational environment.